15-Copper(ii)-containing 36-tungsto-4-silicates(iv) [Cu15O2(OH)10X(A-α-SiW9O34)4]25− (X = Cl, Br): synthesis, structure, magnetic properties, and electrocatalytic CO2 reduction. Issue 35 (22nd August 2018) - Bassil, Bassem S.; Haider, Ali; Ibrahim, Masooma; Mougharbel, Ali S.; Bhattacharya, Saurav; Christian, Jonathan H.; Bindra, Jasleen K.; Dalal, Naresh S.; Wang, Meng; Zhang, Guangjin; Keita, Bineta; Rutkowska, Iwona A.; et al.
Abstract : Two novel Cu15 -containing polyoxometalates are active and selective catalysts for electrochemical CO2 reduction. Abstract : The 15-copper(ii )-containing 36-tungsto-4-silicates [Cu15 O2 (OH)10 X(A-α-SiW9 O34 )4 ] 25− (X = Cl, 1 ; Br, 2 ) have been prepared in 70% yield by reaction of the trilacunary 9-tungstosilicate precursor [A-α-SiW9 O34 ] 10− with Cu 2+ ions in aqueous pH 8 medium. Both polyanions1 and2 were isolated as hydrated mixed potassium/sodium salts and characterized in the solid state by FT-IR, TGA, single-crystal XRD, and elemental analysis. DC magnetic susceptibility measurements from 1.8–300 K established the ground state to be paramagnetic with a magnetic moment corresponding to 15 uncoupled Cu 2+ ( S = 1/2) ions. EPR measurements and simulations were consistent with this analysis. Electrochemical studies were performed for polyanions1 and2 dissolved in solution to elucidate the electroactivity of both copper and tungstate sites. Using2 as a representative example, the electrocatalytic activity towards CO2 reduction upon deposition on a glassy carbon electrode surface, while retaining selectivity relative to hydrogen evolution, was demonstrated.